Targeted Delivery of Chemotherapy Agents Using a Liver Cancer-Specific Aptamer - Meng, Ling; Yang, Liu; Zhao, Xiangxuan; Zhang, Lucy; Zhu, Haizhen; Liu, Chen; Tan, Weihong (PLOS ONE, 2012)
Background Using antibody/aptamer-drug conjugates can be a promising method for decreasing toxicity, while increasing the efficiency of chemotherapy. Methodology/Principal Findings In this study, the antitumor agent Doxorubicin (Dox) was incorporated into the modified DNA aptamer TLS11a-GC, which specifically targets LH86, a human hepatocellular carcinoma cell line. Cell viability tests demonstrated that the TLS11a-GC-Dox conjugates exhibited both potency and target specificity. Importantly, intercalating Dox into the modified aptamer inhibited nonspecific uptake of membrane-permeable Dox to the non-target cell line. Since the conjugates are selective for cells that express higher amounts of target proteins, both criteria noted above are met, making TLS11a-GC-Dox conjugates potential candidates for targeted delivery to liver cancer cells. Conclusions/Significance Considering the large number of available aptamers that have specific targets for a wide variety of cancer cells, this novel aptamer-drug intercalation method will have promising implications for chemotherapeutics in general.